2004
DOI: 10.1093/annonc/mdh385
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolic disease in patients with monoclonal gammopathy of undetermined significance

Abstract: This study demonstrates that patients with MGUS are at increased risk for VTD. Although a clear reason for the pre-thrombotic state in these patients is not currently evident, few risk factors were identified in the group of patients examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 11 publications
2
49
3
1
Order By: Relevance
“…In three smaller series of 310, 174, and 112 patients with MGUS, the rates of VTE were 6Á1%, 7Á5% and 8%, and the median age of the recruited individuals was 67Á5, 68 and 69Á2 years, respectively (Sallah et al, 2004;Srkalovic et al, 2004;Muslimani et al, 2009). In the population-based 'Study of Men Born in 1913', the prevalence of VTE in a cohort of men followed from the age of 50 years to the age of 80 years was 2% at age 67 (Hansson et al, 1997); therefore, in the …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In three smaller series of 310, 174, and 112 patients with MGUS, the rates of VTE were 6Á1%, 7Á5% and 8%, and the median age of the recruited individuals was 67Á5, 68 and 69Á2 years, respectively (Sallah et al, 2004;Srkalovic et al, 2004;Muslimani et al, 2009). In the population-based 'Study of Men Born in 1913', the prevalence of VTE in a cohort of men followed from the age of 50 years to the age of 80 years was 2% at age 67 (Hansson et al, 1997); therefore, in the …”
Section: Discussionmentioning
confidence: 95%
“…In one of those studies, multivariate analysis showed a significant association of VTE with age (>65 years), M-protein higher than 16 g/l, and progression to malignancy (Sallah et al, 2004). In contrast, a case-control study carried out in 166 male patients who were hospitalized and had diagnosis of MGUS (median age 71 years) and 465 agematched control patients who had tested negative for the presence of M-protein failed to find a significant difference in the rate of VTE between the two groups (5Á4% and 4Á9% respectively).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In 2004, Sallah S et al and Srkalovic G et al published in Ann Oncol and cancer respectively (201)(202) two small hospital based studies on the association of monoclonal gammopathy of undetermined significance (MGUS) and subsequent risk of DVT and reported an elevated risk of DVT in MGUS. Kristinsson Y et al (203) conducted a retrospective study on 4, 196,197 veterans hospitalized at least once.…”
Section: Vte In Monoclonal Gammopathy Of Undetermined Significancementioning
confidence: 99%